Loss of Dact1 Disrupts Planar Cell Polarity Signaling by Altering Dishevelled Activity and Leads to Posterior Malformation in Mice - Wen, Jun (American Society for Biochemistry and Molecular Biology, 2010)
Wnt signaling plays a key role in embryogenesis and cancer development. Dvl (Dishevelled) is a central mediator for both the canonical and noncanonical Wnt pathways. Dact1 (Dapper1, Dpr1), a Dvl interactor, has been shown to negatively modulate Wnt signaling by promoting lysosomal degradation of Dvl. Here we report that Dact1-deficient mice have multiple physiological defects that resemble the human neonate disease congenital caudal regression syndrome, including caudal vertebrae agenesis, anorectal malformation, renal agenesis/dysplasia, fused kidneys, and loss of bladder. These urogenital defects can be traced to impaired hindgut formation starting at embryonic day 8.25. Examination of morphological changes and Wnt target gene expression revealed that the planar cell polarity (PCP) signaling is deregulated, whereas the canonical Wnt/β-catenin pathway is largely unaffected in mutant embryos. Consistently, the activity of the PCP signal mediators Rho GTPase and c-Jun N-terminal kinase is altered in Dact1(−/−) mouse embryonic fibroblasts. We further observed alterations in the protein level and the cellular distribution of Dvl in the primitive streak of mutant embryos. An increased amount of Dvl2 tends to be accumulated in the cortical regions of the cells, especially at the primitive streak ectoderm close to the posterior endoderm that lately forms the hindgut diverticulum. Together, these data suggest that Dact1 may regulate vertebrate PCP by controlling the level and the cellular localization of Dvl protein.